Skewed Wealth Distributions: Theory and Empirics - Benhabib, Jess; Bisin, Alberto (Journal of Economic Literature, 2018)
Invariably, across a cross-section of countries and time periods, wealth distributions are skewed to the right displaying thick upper tails, that is, large and slowly declining top wealth shares. In this survey, we categorize the theoretical studies on the distribution of wealth in terms of the underlying economic mechanisms generating skewness and thick tails. Further, we show how these mechanisms can be micro-founded by the consumption–savings decisions of rational agents in specific economic and demographic environments. Finally we map the large empirical work on the wealth distribution to its theoretical underpinnings. (JEL C46, D14, D31, E21, J31)